IPv6 theory, protocol, and practice - Loshin, Peter. (Morgan Kaufmann, 2004)
The second edition of IPv6: Theory, Protocol, and Practice guides readers through implemetation and deployment of IPv6. The Theory section takes a close, unbiased look at why so much time and effort has been expended on revising IPv4. In the Protocol section is a comprehensive review of the specifics of IPv6 and related protocols. Finally, the Practice section provides hands-on explanations of how to roll out IPv6 support and services. This completely rewritten edition offers updated and comprehensive coverage of important topics including router and server configuration, security, the impact of IPv6 on mobile networks, and evaluating the impact of IPv6-enabled networks globally. Pete Loshin's famously lucid explanations benefit readers at every turn, making Ipv6: Theory, Protocol, and Practice the best way for a large diverse audience to get up to speed on this groundbreaking technology. * The comprehensive, accessible, and up-to-date resource needed by network engineers and support staff, product developers and managers, programmers, and marketing professionals * Divided into sections on theory, the protocol's technical details, and techniques for building Ipv6 networks, this book covers not only the protocol but the ways in which the protocol can be integrated into networks. * Covers critical topics in depth, including router and server configuration, security, value assessment, and the impact of Ipv6 on global networks.